An Efficient Intruder Detection System against Sinkhole Attack in Wireless Sensor Networks: A Review - Aggarwal, Rohit; Bansal, Khushboo (International Journal of Computer Sciences and Engineering, 2025)
This Wireless sensor network is deal with sensing the information from deployed area. For data transmission from source node to destination node various routing protocols is used. Due to routing the energy consumption occurred in the network. In wireless sensor network energy consumption is one of the main problems because every node is operated by battery. In wireless sensor network energy utilization is one of the primary issues in light of the fact that each node is operated by battery. In wireless sensor networks, sensors expend energy both in detecting information and transmitting the detected information to a base station. The power utilization for transmitting information is an exponential function of the separation from the sensor to the base station. Power utilization for detecting information is controlled by the kind of sensor and in addition the routing protocol. The issue in this paper is to build the life time of the sensor systems. To have expansive system life time’s everything nodes need to minimize their energy utilization.